Marangoni-driven self-assembly mxene as functional membrane enables dendrite-free and flexible zinc–iodine pouch cells - Liu, Huan (2024)
Zn metal is a promising anode material in aqueous batteries, but the direct use of Zn foil encounters severe issues of dendrite formation and side reactions, causing short cycle life. Conventional thick and rigid insulating protection layers may impede Zn ion diffusion and detach during mechanical deformation of the battery. Herein, a dendrite-free zinc anode is demonstrated by grafting a thin (≈10 nm) Ti3C2Tx MXene functional membrane which is formed via Marangoni-driven self-assembly. The thin MXene membrane initiates uniform nucleation and promotes deposition of (002)-oriented Zn in a lateral growth mode. Meanwhile, the membrane functions as a soft, stress-adaptive, and protective layer to the underneath active zinc. This functional membrane renders Zn anode with improved cycling stability without notable dendrite formation or side-reaction products. Flexible Zn─I2 pouch cells fabricated from the MXene-covered Zn foil (20 µm thick) anode and a modified ZnI2 cathode demonstrate stable capacity up to 1500 cycles and unchanged voltage upon various mechanical deformations. This work affords new insights into designing functional soft membranes for constructing flexible Zn-based energy devices.